Penerapan Media Audio Visual dalam Meningkatkan Minat Belajar pada Pembelajaran Tematik - Dian Eka Lestari; Allinda Hamidah; Annisa Rahmaniyah (IBTIDA', 2020)
The purpose of this action research is to describe: the thematic learning interest using silent audio visual media, the thematic learning interest using motion audio visual media, the change in learning interest of students in grade II at SDN Bulutengger, Sekaran District, Lamongan. This type of research is classroom action research. The analytical method used is a quantitative method. Data collection by holding observations (observations) and documentation. In this study carried out as many as 2 cycles, which in the cycle there are planning, implementation, observation and reflection. Based on the research class action that has been carried out by researchers, in the cycle 1 phase did not experience an increase, whereas in cycle 2 it had increased. The details are as follows: The interest indicator in cycle 1 gained 59%, while the interest indicator in cycle 2 gained 93%. The overall results of the pre-cycle 1 test scored 59, while the overall post-test results in cycle 2 gained 89. The average cognitive value in cycle 1 gained 56.4, while the average cognitive value in cycle 2 gained 90. The average score affective in cycle 1 gained 50.6, while the average affective value in cycle 2 gained 89.8. The average psychomotor value in cycle 1 was 54.4, while the average psychomotor value in cycle 2 was 87.4, and in cycle 2 the category was stated to be very interested.